2011
DOI: 10.1589/rika.26.1
|View full text |Cite
|
Sign up to set email alerts
|

Time Course Changes in Physical Function Following Different Exercise Interventions for Community-Dwelling Elderly Balance and Muscle Strength Exercises

Abstract: The purpose of this study was to conduct different interventions for frail community-dwelling elderly persons and investigate the time course changes in their physical function.[Subjects] The subjects were 51 frail community-dwelling elderly over 65 years of age, classified from category 1 of needing support to category 1 of needing care. [Method] The subjects were divided into a balance exercise group (24 persons) and a muscle strength exercise group (27 persons), according to site, and exercises were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Aging is rapidly progressing in Japan and more elderly people require daily nursing care 1 ) . Many programs have been reported to improve physical function among older people 2 , 3 , 4 , 5 , 6 , 7 , 8 ) . However, it has also been reported that improved physical function does not lead to a more active lifestyle without emotional support 9 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is rapidly progressing in Japan and more elderly people require daily nursing care 1 ) . Many programs have been reported to improve physical function among older people 2 , 3 , 4 , 5 , 6 , 7 , 8 ) . However, it has also been reported that improved physical function does not lead to a more active lifestyle without emotional support 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been reported that improved physical function does not lead to a more active lifestyle without emotional support 9 ) . Health professionals such as physical therapists and public health nurses have recently implemented exercise classes to reduce the need for nursing care 2 , 3 , 4 , 5 , 6 , 7 , 8 ) . Nevertheless, for such health professionals to reach all community-dwelling older persons in the country is economically unrealistic.…”
Section: Introductionmentioning
confidence: 99%